An Investigation into the Channel of Public Expenditure to Boost Industrial Productivity in Pakistan - Jadoon, Atif khan; Batool, Syeda Azra; Sarwar, Ambreen; Javaid, Maria Faiq; Shahwar, Dur a (iRASD Journal of Economics, 2021)
It is a fact that public expenditure has a strong association with industrial productivity. The industrial sector recorded slow growth of 5.43%, which adds 20.90% to the GDP of Pakistan (2017-2018). This study aims to find the effects of public expenditure on Total Factor Productivity (TFP) in the industrial sector of the country. The study constructed two different models. In the first model, the study used time series data from 1975 to 2018, and the growth of adjusted TFP was calculated by the growth accounting method. In the second model, the study collected data from 1977 to 2018 and checked the impact of government expenditure on the TFP growth in the industry. The unit root tests, Ordinary Least Square (OLS), and Vector Error Correction Model (VECM) were employed. The findings of the study revealed that public expenditures on education were significant and positively related to TFP growth in industries. Public expenditure on health, agriculture, and inflation had a significant and positive association with TFP growth in the industries. Foreign direct investment had a negative but significant impact on TFP growth. The results of the present study suggest that industrial productivity can be increased by increasing the expenditure on education and health.